Membangun Masyarakat Cerdas Dalam Literasi Digital - Rahayu, Sri; Kamal, Muhammad Abyan; Junjunan, Aditya Rahma; Hakim, Fawaz Nurjaman; Fauzan, Irfan Muhammad; Isan, Isan Nurul; Nugraha, Rifqi Septian; Setiawan, Wawan; Faishal, Wildan; Wahyuni, Yayu Siti; Hidayah, Zam Zam Munawarul (Institut Teknologi Garut, 2022)
In today's digital era, many people use social media. Starting from children to parents today many use social media. With social media, many people can easily get information. However, with the easy access of the public to information, many negative impacts arise. One of the negative impacts of easy access to information is fake news or what we usually call hoaxes. Because of that, we from the KKN Informatics 14 team are conducting a webinar on digital literacy to provide education to the public, so that people understand the importance of digital literacy. Our hope is that after people take part in this webinar, people will understand the importance of digital literacy. Apart from conducting webinars, we also carry out several activities such as adding public places to Google maps so that the people of Haruman Village can reach them and also creating content about Covid-19 education on Instagram social media.